Eleventh hour security+ : exam SYO-201 study guide - Dubrawsky, Ido (Syngress eleventh hour series., 2010)
Eleventh Hour Network+: Exam N10-004 Study Guide offers a practical guide for those preparing for the Security+ certification exam. The book's 14 chapters provide in-depth discussions of the following topics: systems security; operating system hardening; application security; virtualization technologies; network security; wireless networks; network access; network authentication; risk assessment and risk mitigation; general cryptographic concepts; public key infrastructure; redundancy planning; environmental controls and implementing disaster recovery and incident response procedures; and legislation and organizational policies. Each chapter includes information on exam objectives, exam warnings, and the top five toughest questions along with their answers.